Impact of active intra-complex rest intervals on post-back squat versus hip thrust jumping potentiation - Urbański, Robert; Biel, Piotr; Kot, Sebastian; Perenc, Dawid; Aschenbrenner, Piotr; Stastny, Petr; Krzysztofik, Michał (Scientific reports, 2023)
This study investigated the impact of active rest intervals within a lower body complex training session on post-activation performance enhancement (PAPE) response in amateur soccer players. Twelve soccer players took part in four different experimental conditions. These sessions included 2 sets of lower body complex-paired exercises, each involving 3 repetitions of either back squats or hip thrusts at 90% one-repetition maximum (1RM) as a conditioning activity paired with a broad jump and countermovement jump. Between those exercises in active intra-complex rest interval conditions, participants were performing 8 repetitions of bench press at 75%1RM or, in passive intra-complex rest interval conditions, rested while seated. A significant main effect of a set to increase broad jump length (p = 0.002), countermovement jump height (p = 0.002), and modified reactive strength index (p = 0.005) was revealed, without any significant differences between conditions. Post-hoc comparisons showed a significant increase in broad jump length from baseline to Set-2 (231 ± 13 vs. 234 ± 13 cm; p = 0.003; ES = 0.22). On the other hand, countermovement jump height and modified reactive strength index significantly increased from baseline to Set-1 (34.4 ± 3.6 vs. 35.6 ± 3.9 cm; p = 0.027; ES = 0.31 and 0.4 ± 0.05 vs. 0.45 ± 0.09; p = 0.005; ES = 0.66). Results of this study showed that to sustain a high training density, sports practitioners may incorporate upper body exercises within the intra-complex rest interval during lower limb complex training sessions and still elicit a significant PAPE effect.
Keywords: postura těla; sportovci; Posture; fotbal; Soccer; lidé; cvičení; Sports; Humans; Exercise; sporty; Athletes